Combining Rice Straw Biochar With Leguminous Cover Crop as Green Manure and Mineral Fertilizer Enhances Soil Microbial Biomass and Rice Yield in South China - Xie, Zhijian; Shah, Farooq; Zhou, Chunhuo (Frontiers in Plant Science, 2022)
Whether combining rice-straw biochar (RSB) with leguminous cover crop (LCC) has synergistic effects in rice production is unknown. This study systematically explored the impacts of RSB on mass decomposition and N release from LCC residues after incorporation to acidic paddy soil. Similarly, the effect of combining these two factors on soil nutrient status and microbial biomasses in rice production system were also examined. Five treatments were included: no N fertilizer (CK); 100% N fertilizer (N100); 80% N fertilizer plus RSB (N80B), LCC (N80M) and combination of RSB with LCC (N80BM) respectively. The results indicated that biomass decomposition and N release pattern followed a double exponential decay model such that RSB addition slightly stimulated the rates of both mass decomposition and N release during the initial rapid phase of decomposition. Thereafter, it notably slowed down the rates of both these parameters during the relatively slower stage of incorporating LCC residues to paddy soil during early rice season. Compared to 100% NF, applying 80% NF in conjunction with RSB and/ or LCC residue improved grain yield and its components (i.e., effective panicles, 1000-grain weight and full-filled grains) that subsequently increased N accumulation and physiological use efficiency (PUEN) of rice shoot. Moreover, under 20% NF, applying RSB and/ or LCC residue remarkably increased the soil organic matter and total N, as well as the soil microbial populations and biomasses, while the contents of NH4+ and NO3- were decreased in RSB amended paddy soil (N80B and N80BM), in comparison with N100, respectively. Thus, combining RSB with LCC residue is a novel and promising management intervention for improving soil fertility and rice production in south China.